1985
DOI: 10.1073/pnas.82.15.4979
|View full text |Cite
|
Sign up to set email alerts
|

Human class I alcohol dehydrogenases catalyze the oxidation of glycols in the metabolism of norepinephrine.

Abstract: Investigations of the function of human liver alcohol dehydrogenase (ADH) in norepinephrine metabolism have revealed that class I ADH catalyzes the oxidation of the intermediary alcohols 4-hydroxy-3-methoxyphenyl glycol (HMPG) and 3,4-dihydroxyphenyl glycol (DHPG) in vitro.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

1991
1991
2007
2007

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 22 publications
1
31
0
Order By: Relevance
“…Subsequent studies, involving intravenous infusions of deuterated MHPG, established that most VMA is produced by oxidation of circulating MHPG (Blombery et al, 1980;Mårdh et al, 1983;Mårdh and Ä nggård, 1984). Human class I alcohol dehydrogenase, located mainly in the liver, was then identified as the enzyme responsible for this conversion (Mårdh et al, 1985). …”
Section: B Formation Of Vanillylmandelic Acidmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequent studies, involving intravenous infusions of deuterated MHPG, established that most VMA is produced by oxidation of circulating MHPG (Blombery et al, 1980;Mårdh et al, 1983;Mårdh and Ä nggård, 1984). Human class I alcohol dehydrogenase, located mainly in the liver, was then identified as the enzyme responsible for this conversion (Mårdh et al, 1985). …”
Section: B Formation Of Vanillylmandelic Acidmentioning
confidence: 99%
“…Thus, increased MHPG levels after ethanol do not reflect a shunting in production of DHMA to DHPG. Rather, it is now clear that decreased levels of VMA and increased levels of MHPG after ethanol reflect inhibitory influences on hepatic alcohol dehydrogenase and aldehyde dehydrogenase-catalyzed conversion of MHPG to VMA (Mårdh et al, 1985).…”
mentioning
confidence: 99%
“…As mentioned, the reductive pathway by ADH or ALR/AR is favored in DOPEGAL metabolism whereas the oxidative pathway by ALDH is favored in DOPAL metabolism (Kawamura et al, 1997). In DOPEGAL metabolism, hepatic class I ADH isozymes catalyze the conversion of MHPG to the aldehyde, MOPEGAL (Mardh et al, 1985), which is then converted by hepatic ALDH to VMA (Messiha, 1978). Liver class I ADH enzymes have also been reported to efficiently catalyze the reduction of DOPAL (K m ϭ 8.9 M), and it has been reported that class I ADH is involved in the metabolism of catecholamines (Mardh and Vallee, 1986;Svensson et al, 1999).…”
Section: Alcohol Dehydrogenasementioning
confidence: 99%
“…MHPG enters the systemic circulation and is the major intermediate in the systemic production of vanillylmandelic acid (VMA) (Mardh et al, 1983;Mardh and Anggard, 1984;Eisenhofer et al, 1996a). In this process, MHPG is oxidized by hepatic class I ADH isozymes to the aldehyde, 3-methoxy-4-hy-TOXICITY AND METABOLISM OF DOPAL AND DOPEGAL: ROLE OF ALDH droxyphenylglycolaldehyde (MOPEGAL) (Mardh et al, 1985), which is then oxidized by hepatic ALDH to VMA (Messiha, 1978). As such, the production of VMA from the O-methylation of DOMA represents a minor pathway.…”
Section: A Overviewmentioning
confidence: 99%
“…This is because the enzyme responsible for formation of VMA from MHPG, alcohol dehydrogenase, is localized to the liver (21,22). The substantial production of VMA from circulating DHPG and MHPG, most of which is derived from neuronal norepinephrine metabolism, explains why VMA is a relatively insensitive marker for pheochromocytoma compared with the precursors norepinephrine, epinephrine, normetanephrine and metanephrine (23)(24)(25)(26)(27).…”
Section: Disposition Of Catecholamines Derived From the Sympatho-adrementioning
confidence: 99%